Creation of a New Explosive Injury Equipment to Induce a Rabbit Animal Model of Closed Globe Blast Injury via Gas Shock - Liu, Yuanyuan; Yang, Tiantian; Yu, Jinguo; Li, Mengxuan; Li, Jianan; Yan, Hua (Frontiers in Medicine, 2021)
To establish a rabbit animal model of closed globe blast injury with application of self-developed explosive injury equipment, we tend to explore anatomic and pathological changes of eyes under different gas pressure. The device comprises high pressure air source compression pump, air channel and gas shock. There were 36 healthy bluish blue rabbits exposed to one of five blast pressures (500Kpa, 1000Kpa, 1500Kpa, 2000Kpa, 5000Kpa). Slit lamp microscope, B-mode ultrasonography, fundus photography, optical coherence tomography (OCT) and intraocular pressure (IOP) examination were performed 0, 1, 3 and 7 days post exposure, while gross histopathology was assessed with HE stain at 7 days. Contralateral eyes and non-blast exposed rabbits were used as controls. Definitive evidence of closed globe blast injury was obtained. Corneal edema and hyphema were observed in models under all pressures with no full-thickness globe injury, or lens rupture, the severity of which was pressure independent. There was no obvious retinal abnormality on B ultrasound or OCT scan, while light vitreous hemorrhage, commotio retinae and heavy retinal pigmentation presented on one eye respectively in eyes exposed to 5000Kpa. Increased retinal thickness with disorganizations on the retinal ganglion cell (RGC) layer and RGC apoptosis in groups under higher pressure (＞500Kpa). IOP of injured eyes were statistically decreased at day 1 and 7 post injury (p<0.05). Conclusively, the rabbit animal model induced by self-developed equipment could mimic clinical features of closed ocular blast injury successfully, which was feasible and easy to operate. This will be a new rabbit animal model for investigating mechanisms and new therapeutic interventions of closed globe blast injury in the future.